The genus Gymnodoris Stimpson, 1855 (Mollusca, Nudibranchia) in New Caledonia, with descriptions of eleven new species - de Souza-Canal, Jade; Valdés, Ángel (Zootaxa, 2025)
The genus Gymnodoris Stimpson, 1855 in New Caledonia is studied based on three molecular markers: COI, 16S, and Histone H3, obtained from 183 newly collected specimens. Species were characterized using species delimitation (COI gene) and phylogenetic analyses using all three genes. The data were compared with sequences obtained from GenBank. Most species recovered were found to belong to previously described species, or undescribed species previously reported in the literature. However, 11 species were found to be distinct and those are formally described herein. For these new species, full anatomical descriptions are provided, including reproductive system and radula illustrations and comparisons to other species are provided. An effort was made to try to identify species previously described from New Caledonia with uncertain status with the newly collected material, this resulted in the re-description of Gymnodoris suggens (Risbec, 1928) and the tentative synonymies of Gymnodoris kouaouae (Risbec, 1928) and Gymnodoris perlucens (Risbec, 1928). The phylogenetic hypotheses generated provide no support for the various genus-level names currently synonymized with Gymnodoris.